Model Pengembangan Ekowisata dalam Upaya Pemberdayaan Masyarakat Lokal - Ridlwan, Muhammad Ama; Muchsin, Slamet; Hayat, Hayat (Political Science Program, Universitas Negeri Semarang, 2017)
Today the tourists began to idolize attractions that not only serves its natural beauty alone but rather to intetaksi society, therefore, began to develop the type of special interest is a tourist village. Just as Ecological Tourism Village (KWE) Puspa Cement Universe in the village of Blitar District of Gandusati offers nature tourism and ecotourism education or commonly referred to tourists. With the development of this tourism community will be empowered through tourism activities. This study aims to apply the model of Community Based Tourism (CBT) in the development of tourism in the KWE Puspa Universe and the role of government and society in the development of KWE Puspa universe and to know what are the factors supporting and owned KWE Puspa Universe. This research method using descriptive research with a qualitative approach to collect data in the form of primary and secondary data. The analysis technique used in this study are observation, interviews, and documentation. The results showed that KWE Puspa Universe in the development of ecotourism has been applying the principles of Community Based Tourism (CBT), which can be seen from the activities that were held by KWE Puspa Universe, the role of government and active role in community development makes KWE KWE Puspa Puspa Universe Universe and growing. Then the factors driving and inhibiting owned KWE Puspa Universe in formulating the best strategies in the development of tourism.